Adjunctive Divalproex Versus Placebo for Children With ADHD and Aggression Refractory to Stimulant Monotherapy - Blader, Joseph C. (2009)
OBJECTIVE: The purpose of the present study was to evaluate the efficacy of divalproex for reducing aggressive behavior among children 6 to 13 years old with attention deficit hyperactivity disorder (ADHD) and a disruptive disorder whose chronic aggression was underresponsive to a prospective psychostimulant trial. METHOD: Children received open stimulant treatment during a lead-in phase that averaged 5 weeks. Agent and dose were assessed weekly and modified to optimize response. Children whose aggressive behavior persisted at the conclusion of the lead-in phase were randomly assigned to receive double-blind, flexibly dosed divalproex or a placebo adjunctive to stimulant for 8 weeks. Families received weekly behavioral therapy throughout the trial. The primary outcome measure was the proportion of children whose aggressive behavior remitted, defined by post-trial ratings of negligible or absent aggression. RESULT: A significantly higher proportion of children randomly assigned to divalproex met remission criteria (eight out of 14 [57%]) than those randomly assigned to placebo (two out of 13 [15%]). Divalproex was generally well tolerated. CONCLUSIONS: Among children with ADHD whose chronic aggressive behavior is refractory to optimized stimulant treatment, the addition of divalproex increases the likelihood that aggression will remit. A larger trial is necessary to specify with greater precision the magnitude of benefit for adjuvant divalproex.